Controlled aliasing in parallel imaging results in higher acceleration (CAIPIRINHA) for multi‐slice imaging - Felix Breuer; Martin Blaimer; Robin M. Heidemann; Matthias Mueller; Mark A. Griswold; Peter M. Jakob (2005)
Abstract In all current parallel imaging techniques, aliasing artifacts resulting from an undersampled acquisition are removed by means of a specialized image reconstruction algorithm. In this study a new approach termed “controlled aliasing in parallel imaging results in higher acceleration” (CAIPIRINHA) is presented. This technique modifies the appearance of aliasing artifacts during the acquisition to improve the subsequent parallel image reconstruction procedure. This new parallel multi‐slice technique is more efficient compared to other multi‐slice parallel imaging concepts that use only a pure postprocessing approach. In this new approach, multiple slices of arbitrary thickness and distance are excited simultaneously with the use of multi‐band radiofrequency (RF) pulses similar to Hadamard pulses. These data are then undersampled, yielding superimposed slices that appear shifted with respect to each other. The shift of the aliased slices is controlled by modulating the phase of the individual slices in the multi‐band excitation pulse from echo to echo. We show that the reconstruction quality of the aliased slices is better using this shift. This may potentially allow one to use higher acceleration factors than are used in techniques without this excitation scheme. Additionally, slices that have essentially the same coil sensitivity profiles can be separated with this technique. Magn Reson Med 53:684–691, 2005. © 2005 Wiley‐Liss, Inc.